Psychological assessment in infertility: A systematic review and meta-analysis - Tavousi, Sayed Abolfazl; Behjati, Mohaddeseh; Milajerdi, Alireza; Mohammadi, Amir Hossein (Frontiers in Psychology, 2022)
Infertility is a prevalent worldwide health issue and is defined by the World Health Organization (WHO) as a global health problem. Considering the importance of the psychological dimensions of infertility, various measurement tools have been used to measure the variables involved in infertility, of which the most widely used are the following: the Symptom Checklist 90 (SCL90), the Brief Symptom Inventory (BSI), the State-Trait Anxiety Inventory Form (STAI), and the Depression Anxiety Stress Scale (DASS). Therefore, given the problems of infertile people in terms of psychological dimensions, the aim of this meta-analysis was to assess the psychological assessment score in infertility. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, we applied an online database with no time restriction. Data were gathered using a random-effect model to estimate the standard mean difference (SMD) for the evaluation of the strength of association analyses. Our data demonstrated a significant higher SCL90 score (CISCL90: 0.96, 0.34–1.57, heterogeneity: 94%, pheterogeneity < 0.001), and a non-significant higher DASS score (CIAnxiety: 0.82, -0.14 to 1.79; CIDepression: 0.8, -0.28 to 1.87; and CIStress: 0.82, -0.24 to 1.88). It is essential to seek for strategies to help infertile patients overcome their infertility-related psychological problems.